Family planning among Orang Asli women in District of Hulu Langat Selangor Darul Ehsan, 1994 - Jamsiah Mustafa,; Hanafiah Mohd Salleh, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
An analytic cross-sectional study of married Orang Asli was carried out in the district of Hulu Langat, Selangor D.E., to examine the practice of family planning and the, factors influencing it. The collection of data completed within 4 weeks that is from 20.12.93- 2.1.94 and 16.5.94 - 29.5.94. The study used the universal sampling method. Home visit were made to all the 10 Orang Asli villages in order to interview the respondents through the used of guided questionnaires prepared in Bahasa Malaysia. The finding showed that 98.33% of respondents have knowledge of at least one type of effective method of family planning with the pill being the most well known method. The study also showed that 86.67% knew of in effective method. Theused of plant roots was the method known by the majority of the respondents. The study found that 51.64% practised family planning while 25.41% did not practised it. The remaining of 22.95% were pregnant at the time of data collection. The finding also showed that only 16.390; of respondents practised in effective method in comparison to 34.43% who practised the effective method. One respondent ( 0.82% ) practised both method simultaneously. Statistical tests were carried out to discover whether relationship exist between the two (2) dependent variables of knowledge and practise with independent variables of socioeconomic status, age, gravida and number of living children. However X2 and t-test did not show any sjgnificant relationship between the two (2) dependent variables and the independent variables. The main factor that influenced the respondents to plan their families was to space the pregnancy. Other important factor was the encouragement from the husband. The main factor that obstructed the used of family planning was they felt that they were still young. Other important factors were their desire for a big family and a lack of accurate knowledge of the importance of birth spacing on maternal and child health.